Simulation and Long-Range Planning for Resource Allocation - Rauner, Robert M.; Steger, Wilbur A. (Quarterly Journal of Economics, 1962)
Introduction, 219. — The problem setting: planning for a new complex system, 221. — The logistics laboratory simulation, 224. — Simulation models, 225. — The game simulation procedure, 229. — Results, 230. — Other features of the laboratory game simulation, 233. — Assessment, 239. — Conclusion, 244.